PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA SOSIAL TERHADAP KINERJA PEGAWAI PT TELEKOMUNIKASI INDONESIA (TELKOM) WILAYAH KOTA TASIKMALAYA - Desty Putri Djayanti; Syamsul Hadi Senen; Eded Tarmedi (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
This research aims to find out the effectiveness of leadership, social work environment, and performance. The design of this study is cross sectional using an explanatory approach to surveys. The analysis unit used is a saturated sample of 100 employees. This research uses quantitative methods. With the data analysis technique used is a double linear regression with SPSS computer software version 26.0. The results of the study can be known that 1) the level of leadership is in a very high category, 2) the level of social work environment is in a very high category, 3) the performance level is in the high category, 4) leadership has an influence of 58.3% on performance, 5) the social work environment has an influence of 56.8% on performance, and 6) the influence of leadership and social work environment on performance is 70.7%. From the results of hypothetical testing research, it can be known that leadership and social work environment have a significant effect on performance.Azizah, A., Gustomo, A. (2015). The Influence of Employee Engagement to Employee Performance. Business and Management, 4(7), 817–829. http://etd.uum.edu.my/2541/Esther, M. (2011). An analysis of the effect of corporate governance on performance of commercial state corporations in Kenya. Business and Public Management, 1(1), 90–101.Giri, V. N., Kumar, B. P. (2010). Assessing the Impact of Organizational Communication on Job Satisfaction and Job Performance. 55(June), 137–143. https://doi.org/10.1007/s12646-010-0013-6Hadi Senen, S., Masharyono, M., Triananda, N., Sumiyati, S. (2016). The Employee Performance Influenced by Communication: a Study of BUMD in Indonesia. 15, 596–598. https://doi.org/10.2991/gcbme-16.2016.111Hameed, A. (2011). Employee Development and Its Affect on Employee Performance A Conceptual Framework. 2(13), 224–229.Hartati, W. (2018). Program Pelatihan dan Kinerja Pada Industri Perbankan Syariah. Manajemen Bisnis, 7(2), 117–124.Madan Poonam, Kaur, B. J. (2016). Critical success factors in enterprise resource planning implementation: a review of case studies. Journal of Enterprise Information Management, 29(1).Masharyono, Senen, S. H. (2015). Job Performance Analysis Temporary Employee Administrative with Competence and Job Characteristics in Supporting Universitas Pendidikan Indonesia Leading and Outstanding Achieve. Fokus Ekonomi, 10(2), 119–137.Moulana, F., Sunuharyo, B. S., Utami, H. N. (2017). Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Variabel Mediator Motivasi Kerja (Studi pada Karyawan PT. Telkom Indonesia,Tbk Witel Jatim Selatan, Jalan A. Yani, Malang). 44(1), 178–185.Noorlesmana, P. P., Rustono, A. (2018). Pengaruh budaya organisasi dan motivasi kerja terhadap kinerja karyawan di PT Telekomunikasi Indonesia Witel Bandung.Odunlami, I. B., Matthew, A. O. (2014). Compensation Management and Employees Performance in the Manufacturing Sector , A Case Study of a Reputable Organization in the Food and Beverage Industry. 2(9), 108–117.Osa, I. G. (2014). Monetary Incentives Motivates Employee’s On Organizational Performance. Arts Humanities and Social Sciences, 2(7), 61–69.Parent, J. D., Lovelace, K. J., Parent, J. D., Lovelace, K. J. (2018). Employee engagement , positive organizational culture and individual adaptability Employee engagement , positive organizational culture and individual adaptability. https://doi.org/10.1108/OTH-01-2018-0003Rahmawati. Sumiyati. Masharyono. (2016). Leader Member Exchange Dan Kepribadian Untuk Meningkatkan Employee Voice Kopontren DT. Strategic Jurnal Pendidikan Manajemen Bisnis, 11(20), 38–44.Robbins, S., Judge, T. (2015). Perilaku Organisasi (16th ed.). Salemba Empat.Sugiyono. (2009). Metode Penelitian Pendidikan: Pendekatan Kuantitatif, Kualitatif dan RD. Bandung: Alfabeta.Sedarmayanti. (2011). Manajemen Sumber Daya Manusia, Reformasi Birokrasi dan Manajemen Pegawai Negeri Sipil (Kelima). PT Rafika Aditama.Sutedjo, A. S., Mangkunegara, A. P. (2018). Pengaruh Kompetensi dan Motivasi Kerja terhadap Kinerja Karyawan di PT. Inti Kebun Sejahtera. BISMA (Bisnis Dan Manajemen), 5(2), 120. https://doi.org/10.26740/bisma.v5n2.p120-129Takasenseran, M. C., Mandey, S. L., Kojo, C. (2014). Factor for Employees Efectiveness Specially At Public Organization , Which Make Leader Have To Pay Attention By Giving a Condusif Work Environment for Employees To Make Positif and Good Relationship With the Leader . Jurnal Pengaruh Lingkungan Kerja, 2(3), 1726–1736.Usman Ali, W., Rizwan Raheem, A., Nawaz, A., Imamuddin, K. (2014). Impact of Stress on Job Performance: An Empirical study of the Employees of Private Sector Universities of Karachi, Pakistan. Research Journal of Management Sciences, 3(7), 14–17. http://ssrn.com/abstract=2463554